Intra-socket application of Hyaluronic acid reduces pain and swelling following wisdom teeth removal - Sultana Shuborna Nadia; Khoo Lee Kian; Bhattarai Bishwa Prakash; Chaiyasamut Teeranut; Kiattavorncharoen Sirichai; Pairuchvej Verasak; Wongsirichat Natthamet (EDP Sciences, 2022)
Background: Hyaluronic acid (HA) has the potential to promote wound healing. Pain and swelling with trismus are common sequalae post wisdom teeth removal. This study aims to investigate the effectiveness of intra-socket HA solution to reduce these uncomfortable post-operative events. Materials and methods: 30 patients underwent bilateral extractions of mandibular wisdom teeth for this study. Intra-socket application of 0.7 ml 20 mg/2 ml HA solution (Hyalgun) with Gel foam as a scaffold in study site versus Gel foam only on control site was conducted via a split mouth study design. Data collection of five facial reference points for swelling and maximum mouth opening was recorded during the pre-operative period and post-operative 2nd and 7th day. The VAS pain score at post-op 1st, 2nd and 3rd day and the number of analgesics for the 7-day post-operative duration were evaluated. Results: The HA group demonstrated statistically significant less swelling, trismus and analgesia consumption on the 2 and 7 days after surgery. VAS scores on day 1, 2 and 3 after surgery (P = 0.05) were significantly less in the HA group compared to the control group. Conclusion: The application of intra-socket HA has a positive effect for reducing postoperative pain and swelling with trismus after the lower third molar intervention (LTMI).